Transgenerational plasticity in salinity tolerance of rice unraveling non-genetic phenotypic modifications and environmental influences - Aycan, Murat (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For commercial re-use, please contact reprintsoup.com for reprints and translation rights for reprints. All other permissions can be obtained through our RightsLink service via the Permissions link on the article page on our site—for further information please contact journals.permissions@oup.com.